Bel-Ami and the myth of androgynous: the encounter with the other - Santos, Kedrini Domingos dos (Lettres Françaises, 2013)
This article aims to verify the actualization of the myth of the androgyne in the novel Bel-Ami (1885), of the French writer Guy de Maupassant (1850-1893). The myth can be thought consistent with the pursuit of perfection, which binds to the primordial unity. In the novel, this unit appears in the search for the other, is that although an autonomous existence, established itself as the half remaining to complete a lifetime lover. These issues are addressed in the novel so peculiar, showing pessimism of Maupassant, for whom it is impossible to achieve the ideal love.